Business Strategy Formulation For Tourism Bus (Case Study: Po Gunung Sembung Putra) (The Indonesian Journal of Business Administration, 2021)
PO Gunung Sembung Putra is a tourist bus company that offers bus rental services for tourism activities. The company has loyal customers and it has been managed traditionally as a family business. Sales is relying on the pool of loyal customers. There is limited standard operating procedures in managing the bus fleet. Human resources are organised based on familial system. As the number of trips in Indonesia continues to increase, the number of sales at PO Gunung Sembung Putra has continued to decline.The purpose of this research is to help PO Gunung Sembung Putra increase the number of sales by formulating operational, marketing and human resource strategies that aim to solve these problems. This study analyses the business problem by conducting PESTEL, porter five forces, competitor analysis, STP analysis, marketing mix, and resource based analysis. After finding the root of the problem, the writer will propose a SWOT analysis, EFAS IFAS and the TOWS matrix as a guide. This study will also provide recommendations and implementation plan within one year to assist decision making for the PO Gunung Sembung Putra.Keywords: Business strategy, transportation, tourism bus